THE INFLUENCE OF MODERN HRM PRACTICES, PERFORMANCE-BASED WORK INCENTIVES, AND FLEXIBLE WORK MODELS ON EMPLOYEE PERFORMANCE IN THE "NEW WORK" ERA - SRI NDARU ARTHAWATI; Eloh Bahiroh (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The New Work era, characterised by digital disruption, hybrid work, and post-pandemic adaptation demands, has forced a paradigm shift in human resource management in Indonesia. Modern HRM practices such as AI-driven recruitment and digital training, performance-based work incentives through transparent gamification, and flexible work models such as flextime-hybrid arrangements synergistically influence multidimensional employee performance (task, contextual, adaptive) with an increase in effectiveness of up to 30-40% based on a synthesis of literature reviews. The research results identify key causal patterns through narrative thematic analysis, showing that High-Performance Work Systems (HPWS) that integrate these three elements mediate through AMO theory and job autonomy, with the strongest effect from work flexibility (β=0.38-0.42) in the context of Indonesia's collectivist culture, which faces challenges of social isolation and work-family conflict. while a significant gap lies in the lack of longitudinal studies on adaptation fatigue and AI-incentive ethics. The findings produce practical recommendations for HR practitioners in Indonesian technology companies and MSMEs to design holistic policies based on technological transparency and national digital infrastructure to increase sustainable productivity and global competitiveness, in line with Sustainable Development Goal 8 on decent work, with theoretical implications in the form of enriching the CMO (Context-Mechanism-Outcome) framework for future HRM research.